Clinical and pathological characteristics of epidermal cysts in hairless extremities - LU Bo; GAO Teng; ZHAO Liping; ZHANG Shifa (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Objective To investigate the characteristics of epidermal cysts in hairless extremities. Methods The clinical data of 3 cases of epidermal cysts were collected, and their clinical and pathological characteristics were analyzed. Results Disease duration ranged from 4 months to 1 year. Patient 1 had a lesion on the palmar side of the second finger of the right hand after a trauma. Patients 2 and 3 had lesion on the sole and lateral side of the foot, respectively, with no history of trauma. Histopathological examination showed that the cyst walls were composed of multiple lamellar squamous epithelium and granular layers, and the cyst cavity was filled with keratin, consistent with the histopathological changes of typical epidermal cysts. Following surgical removal of the cysts, no recurrence was observed during six-month follow-up. Conclusions The epidermal cysts in hairless parts of the extremities have a short onset time, without opening surface, eruption or secretion. The pathological changes are the same as those in hairy parts of the epidermal cysts. The preferred treatment is complete surgical resection.